2018
DOI: 10.1101/347724
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Chromosomal fusion and life history-associated genomic variation contribute to within-river local adaptation of Atlantic salmon

Abstract: Chromosomal inversions have been implicated in facilitating adaptation in the face of high levels of gene flow, but whether chromosomal fusions also have similar potential remains poorly understood. Atlantic salmon are usually characterized by population structure at multiple spatial scales; however, this is not the case for tributaries of the Miramichi River in North America. To resolve genetic relationships between populations in this system and the potential for known chromosomal fusions to contribute to ad… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 107 publications
0
22
0
Order By: Relevance
“…More points of comparison would help to show whether certain chromosomes or particular motifs found in chromosomes might be more prone to rearrangements than others. Furthermore, the dynamic fission and fusion of the gene‐rich microchromosomes may have implications regarding species or clade‐specific adaptation (Guerrero & Kirkpatrick, ; Hansmann et al, ; Wellband et al, ). Physically creating or breaking linkages between sets of genes will change the local recombination rates.…”
Section: Discussionmentioning
confidence: 99%
“…More points of comparison would help to show whether certain chromosomes or particular motifs found in chromosomes might be more prone to rearrangements than others. Furthermore, the dynamic fission and fusion of the gene‐rich microchromosomes may have implications regarding species or clade‐specific adaptation (Guerrero & Kirkpatrick, ; Hansmann et al, ; Wellband et al, ). Physically creating or breaking linkages between sets of genes will change the local recombination rates.…”
Section: Discussionmentioning
confidence: 99%
“…However, without information on individual phenotype and ecological data, our conclusions regarding the adaptive nature of the rearrangements remain speculative. Nevertheless, recent work from a river system in North America (Miramichi River, New Brunswick, Canada) also identified variation in the Ssa08/29 chromosomal fusion and found that the frequency of the fusion was associated with precipitation, suggesting a potential role in local adaptation (Wellband et al, ). Many salmonid species show differences in karyotypes (Phillips, ) and although limited studies suggest that some identified rearrangements may not be involved in adaptive differences between individuals (Thorgaard, ), the identification of rearrangements coupled with advances in genomic technologies will allow better characterization of the adaptive or neutral role of rearrangements in salmonids.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, linked genomic architectures have been associated with a variety of adaptive traits in natural populations ( Table 1 ). Although inversions appear to be the most commonly studied ( Wellenreuther and Bernatchez 2018 ; Wellenreuther et al 2019 ), chromosomal fusions ( Wellband et al 2019 ) and complex architectures involving multiple rearrangements ( Tigano et al 2018 ; Pearse et al 2019 ) are also associated, directly or indirectly, with traits relevant for adaptation. In some cases, SNPs located in proximity to one another are found to be in LD and the structural architecture is yet to be determined (e.g., Micheletti et al 2018 ).…”
Section: Linked Genomic Architectures Underlie Diverse Traits In Natumentioning
confidence: 99%
“…Chromosomal translocations and fusions are common among salmonids ( Phillips 2005 ). Their adaptive significance, if any, is not generally known, although a fusion in Atlantic salmon (Ssa08/Ssa29) is associated with summer precipitation in a Canadian river system ( Wellband et al 2019 ).…”
Section: Linked Genomic Architectures Underlie Diverse Traits In Natumentioning
confidence: 99%